Ideology, ethics and policy development in public service interpreting and translation - Valero Garcés, Carmen; Tipton, Rebecca (Translation, interpreting and social justice in a globalised world, 2017)
This collection of new research on public service interpreting and translation (PSIT) focuses on ideology, ethics and policy development. It provides fresh perspectives on the challenges of developing translation and interpreting provision in service contexts and on the tensions between prescribed approaches to ethics and practitioner experience.